A governance framework for umgeni water's board with specific reference to the King III and King IV reports - Makhaye, Jabulani (University of the Free State, 2017)
Umgeni Water is not an SOE but a National Government Business Enterprise (See Schedule 3 (Part B) of the PFMA. SOE’s are also not funded by the National Revenue Fund. Government provides guarantees-such as in the case of SAA, ESKOM, etc. SOE’s are supposed to function on a profit base. SOE’s do not appear in the national budget. Improving the governance performance of SOEs is very important, as is the transformation of board practices in South Africa in line with the adopted King III and King IV Reports and the Companies Act (No. 71 of 2008), Sections 30 and 66 to 78; the Public Finance Management Act (PFMA) (No. 1 of 1999), Section 77; and Treasury Regulation 27.1.1. Governance framework transformation for SOEs in order to achieve their objectives or their mandate is highly imperative as set out by the central government through its legal framework. In terms of the Constitution of the Republic of South Africa (Act No. 108 of 1996), and as guided by the Water Services Act (No. 108 of 1997), the water utility provides water to the citizens of the country. The South African government is the sole shareholder, having 100% ownership, managed by a Board (Umgeni Water Board) who is also the accounting authority in terms of Section 49 of the PFMA. This research also focuses on the role of the government in relation to the oversight role through parliament committees’ portfolio committees, such as the Standing Committee on Public Accounts (SCOPA) and the Portfolio Committee on Water and Sanitation. Government ownership means that the state is responsible for ensuring that SOEs’ governance framework and best practices, according to the King III and King IV Reports, are in place and that the board functions effectively and efficiently and is supported financially in order to execute the government mandate. Hendrikse and Hefer-Hendrikse (2014:104) state that corporate governance is a partnership of shareholders, directors, and management to provide wealth creation and economic wellbeing to the wider community of stakeholders. Hendrikse and Hefer-Hendrikse (2014:104) further state that good corporate governance should be thought of as a basic business common sense framework in which companies can systematically pursue superior performance and enhance shareholder value. The aim of this study is to explore the governance framework with specific reference to the King III and King IV Reports with the aim of improving on, if any, the governance framework. The King III Report also differentiate between national government business enterprises and national public entities. See also Section 52 of the PFMA for differentiation between public entity and government business enterprises. Umgeni Water was selected among the two water utilities in KwaZulu-Natal managed by a Board in terms of Section 49 of the PFMA.
Keywords: State-owned enterprise (SOE); Compliance; Stakeholders; Risk management; Corporate governance; Dissertation (M.Sc. (Governance and Political Studies)--University of the Free State, 2017